United States : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
The note delves on the U.S. housing market outlook, the potential benefits of mitigating distressed sales household deleveraging, and the recovery. Policies to facilitate labor market adjustment to reduce the large employment volatility without affecting efficient labor allocation could prevent problems. U.S. firms are hoarding money but it is likely to be spent to boost firms' capital expenditure, rather than kept as precautionary balances. The note discusses commodity price shocks affecting Treasury inflation protected securities (TIPS), budget institutions for federal fiscal consolidation, and mortgage delinquencies in the United States.